Egypt’s low carbon hydrogen development prospects - Habib, A; Ouki, M (Oxford Institute for Energy Studies, 2021)
Egypt has one of the largest economies in the Middle East and North Africa (MENA) region and several of its industries are large sources of greenhouse gas (GHG) emissions. As part of its contribution to mitigate GHG emissions within the framework of the 2015 Paris Agreement on climate change, Egypt is focusing on the development of an ambitious renewable energy programme.